2016
DOI: 10.1017/s1368980016000306
|View full text |Cite
|
Sign up to set email alerts
|

Food insecurity among people who inject drugs in Los Angeles and San Francisco

Abstract: Objective: We estimated the prevalence of food insecurity among people who inject drugs (PWID) in Los Angeles and San Francisco and explored correlates of food insecurity. Design: A cross-sectional study that measured 30 d food insecurity using the US Adult Food Security Survey ten-item Module developed by the US Department of Agriculture. Food insecurity was defined as including low and very low food security. Setting: Two cities in the state of California, USA. Subjects: Male and female active PWID (n 777). … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

5
25
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 21 publications
(30 citation statements)
references
References 35 publications
5
25
0
Order By: Relevance
“…Numerous population-based studies in the United States and Canada have demonstrated cross-sectional associations between FI and the use of crack [7], methamphetamine [8] and other illicit substances [914]. Consistently high rates of FI and/or malnutrition have also been reported in studies of people who use illicit substances [1518], injected drugs [1924] and crack [25].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Numerous population-based studies in the United States and Canada have demonstrated cross-sectional associations between FI and the use of crack [7], methamphetamine [8] and other illicit substances [914]. Consistently high rates of FI and/or malnutrition have also been reported in studies of people who use illicit substances [1518], injected drugs [1924] and crack [25].…”
Section: Introductionmentioning
confidence: 99%
“…Most of these studies have assumed that substance use contributes to FI, either by draining material resources [7,9,14,19,20,22,24,26] or by imposing a chaotic, marginalized life-style upon users [7,16,18,22,26,27]. Few studies, however, have considered that FI may also act as a structural driver of substance use.…”
Section: Introductionmentioning
confidence: 99%
“…Several authors stress the need for more studies, and suggest multi-body site sampling [9, 21]. Perineal colonization with S. aureus was first described in the 1950s [34], but recent studies are sparse and the clinical importance of perineal carriage in relation to nasal carriage is still unclear.…”
Section: Introductionmentioning
confidence: 99%
“…[ 19 , 20 , 39 42 ] In homeless populations in resource-rich countries like the US, the reported prevalence of food insecurity ranged from 49–94%. [ 19 , 20 ] For people who inject drugs, the prevalence of food insecurity has been reported in the range of 58–71%;[ 41 , 43 ] for illicit non-injection drug use, the prevalence is 34–36%. [ 42 , 44 ]…”
Section: Discussionmentioning
confidence: 99%